The impact of corporate governance on firm performance: empirical evidence from vietnamese listed companies - Tran, Le Thu Ha (2020)
Based on a sample of 97 companies listed on the Hochiminh Stock Exchange and Hanoi Stock Exchange in a five-year period from 2014 to 2019, the dissertation examines the impacts of corporate governance on firm performance in the context of an emerging country like Vietnam. The corporate governance mechanism is proxied by the board size, number of non-executive members on board, chairman ownership, executive board size, CEO duality, CEO ownership, ownership concentration and foreign ownership. Meanwhile, the firm performance is measured by four indicators which belong to three different types of measurements including: accounting measurements (ROA and ROE), market-value measurements (Tobin’s Q), and mixed measurements of accounting value and market-value (Z-score). The dissertation has found that there exists a relationship between corporate governance and firm performance, although that influence is very complicated. The factors such as board size, chairman ownership, and CEO ownership have negative impacts on the performance of companies. On the contrary, number of nonexecutive members on board, executive board size, ownership concentration and foreign ownership contribute positively to the operational effectiveness of firms. However, the relationship between CEO duality and organizational performance is inconclusive since empirical evidence suggest conflicting results.